Außenpolitik vor Ausbruch der Berlin-Krise (Sommer 1955 bis Herbst 1958) - Wettig, Gerhard 1934- (Quellen und Darstellungen zur Zeitgeschichte, 2016)
Published for the first time, Khrushchev`s secret conversations, consultations, and notes document his attitude toward the West. A key issue in the period under consideration was the fate of East Germany. Other important issues include the disarmament overtures made toward the US/NATO, efforts to form an anti-imperialist front with the nations of the Third World, and Khrushchev`s support for anti-colonialist forces